Gir lion : Panthera leo-persica : a natural history, conservation status, and future prospect - SINGH, H. S. (Pugmark Qmulus Consortium, 2007)
This book on "The Gir lion" covers every aspect of the Asiatic lion, including the past and the present status and likely future scenario, and also contains an account of about two decade's of the author's observations on the big cats in the Gir forest.
Keywords: IFoS as an author; Indian Forest Service; India-Gir Forest National Park; Lion